2009
DOI: 10.1176/appi.ajp.2008.08010089
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Maternal Infection and Executive Dysfunction in Adult Schizophrenia

Abstract: Objective Executive dysfunction is one of the most prominent and functionally important cognitive deficits in schizophrenia. Although strong associations have been identified between executive impairments and structural and functional prefrontal cortical deficits, the etiological factors that contribute to disruption of this important cognitive domain remain unclear. Increasing evidence suggests that schizophrenia has a neurodevelopmental etiology, and several prenatal infections have been associated with risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 30 publications
5
142
4
2
Order By: Relevance
“…34 In addition to an association with deviations during adolescence, TMT impairment in patients with schizophrenia has also been associated with deviations during fetal life (in utero maternal infection exposures). 8 Furthermore, non-right-handedness, including mixed-and lefthandedness, which is considered to result from early neurodevelopmental "failure to establish cerebral asymmetry," 23 is more frequent in patients with schizophrenia than in healthy individuals 23 and is associated with executive impairments. 12 Finally, NSS, referred to as the minor, nonlocalizable defects in motor coordination, motor integration and sensory integration, 11 are a clinical marker of pre-and perinatal deviance; 22,35 are much more frequent in patients with schizophrenia and their siblings than in controls; 36 and are associated with cognitive deficits, including executive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In addition to an association with deviations during adolescence, TMT impairment in patients with schizophrenia has also been associated with deviations during fetal life (in utero maternal infection exposures). 8 Furthermore, non-right-handedness, including mixed-and lefthandedness, which is considered to result from early neurodevelopmental "failure to establish cerebral asymmetry," 23 is more frequent in patients with schizophrenia than in healthy individuals 23 and is associated with executive impairments. 12 Finally, NSS, referred to as the minor, nonlocalizable defects in motor coordination, motor integration and sensory integration, 11 are a clinical marker of pre-and perinatal deviance; 22,35 are much more frequent in patients with schizophrenia and their siblings than in controls; 36 and are associated with cognitive deficits, including executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Serologically documented infections in utero were found to be associated with subsequent impaired performance in the executive domain in patients with schizophrenia. 8 An association between lower birth weight, a global proxy measure of uterine "optimality," 9 and neurocognitive deficits has also been found in patients with schizophrenia-spectrum disorders compared with controls. 10 In this context, the aim of our study was to investigate the influences of early brain deviation on executive deficit in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, one can get to the same destination via different routes. For instance, in neuropsychiatric diseases such as autism, schizophrenia, or depression, although men and women may be given a similar diagnosis, there exist significant sex differences in overall rates, timing of onset, symptom presentation, and treatment efficacy (Heim and Nemeroff, 1999;Heim and Nemeroff, 2001;Sanchez et al, 2001;Goldstein et al, 2002;Heim et al, 2004;Bale, 2006;Brown and Susser, 2008;Bale, 2009;Brown et al, 2009;Heim et al, 2009;Bale et al, 2010;Heim et al, 2010;Brown, 2012;Davis and Pfaff, 2014;Goldstein et al, 2014). Further, mechanistic animal studies modeling endophenotypes of these disorders have demonstrated robust sex differences in the timing of susceptibility to insults to the developing brain where males appear more vulnerable prenatally and females postnatally (Mueller and Bale, 2006;Mueller and Bale, 2007;Ivy et al, 2008;Kapoor et al, 2008;Mueller and Bale, 2008;Kapoor et al, 2009;Ivy et al, 2010;Hsiao and Patterson, 2012).…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 99%
“…Epidemiological studies relating to antibody titers against various viruses indicate that viral infection could be the cause of immune dysfunction in one subgroup of schizophrenics 2 . Several viral infections have been associated with the risk of this disorder [3][4][5] . During antiviral immunity, accurate control of the balance between the type I and type II Thelper cells (Th1 and Th2) is pivotal for optimizing immune response 6 .…”
Section: Introductionmentioning
confidence: 99%